MANAGEMENT OF STATE LOCAL GOVERNMENT JOINT ACCOUNT AND LOCAL GOVERNMENT SERVICE DELIVERY IN GOMBE STATE (2013-2018) - Ibrahim, Abdulkadir Ibrahim; Tukur Hassan, Hassan (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
It was difficult for the Federal government to administer successfully all the functions of government through the central organ of the state. It is on this account that local government were created to meet the aspirations of the local populace, and be given constitutional recognition as a third tier organ of government in the 1976 local government reform and 1999 Constitution as amended. It is felt that local government had a pivotal role to play in improving the general standards of local dwellers through the provision of essential services such as the provision of portable water, electricity, construction of local access roads, bridges and culverts, primary health care services, primary education, etc. However, this has been mitigated through improper management of statutory account called State Local Government Joint Account. This study examines the effect of management of state local government joint account on local government service delivery in Gombe State. Various literatures were reviewed and the Theory of Fiscal Federalism was also adopted as a theoretical framework in order to explain the financial relationship between the state and local governments and how this relation affects local government service delivery. The study adopts Documentary Method where the data for the study was generated through secondary sources. The study reveals that the management of state local government joint account has negatively affected local government service delivery due to the high level of unnecessary deductions. Consequently the local governments were unable to discharge their constitutional roles in touching the lives of the people. The study concludes that the Management of State Local Government Joint Account has adversely affected the local government service delivery in Nigeria and more specifically Gombe State in particular. Finally, the study recommends for the abolition of the State Local Government Joint Account as it places the local governments at a disadvantage position.